PENERAPAN MEDIA PEMBELAJARAN BERBASIS LINGKUNGAN DAN PERMAINAN TRADISIONAL (BOY-BOYAN) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BANGUN RUANG DAN SATUAN JARAK SISWA KELAS VI UPT SDN 43 GRESIK - Mohammad Dimas Yanuardana; Agung Setyawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
Mathematical concepts are abstract, while students think concretely. Students' understanding is easier when connected with concrete objects around students. As at UPT SDN 43 Gresik who had difficulty working on questions about counting operations for distance units and building spaces in grade 6. This study aims to find out how the application of environmental-based learning media and traditional games (boy-boyan) to improve learning outcomes of mathematics in building materials. and the distance unit for grade 6 students at UPT SDN 43 Gresik. The researcher presents the results of research quantitatively descriptive of learning Mathematics by using descriptive methods with a quantitative approach. The location of this research is in Pancor, Sidogedungbatu, Sangkapura-Gresik, East Java on Monday, February 27, 2023. The subjects of the research are the 6th grade students of UPT SDN 43 Gresik, totaling 12 people and the object is the students' mathematics learning outcomes. The instruments used were observation of student activities, interview guidelines, and multiplechoice tests (pre-test and post-test). Then, the data collection techniques are observation, interviews, and tests. The data analysis technique is descriptive quantitative. In cycle 1, mathematics learning outcomes are still low. Meanwhile, in cycle 2, mathematics learning outcomes increased. It can be concluded that the application of environmental-based learning media and traditional games (boy-boyan) has an effect on the results of the first and second cycles of research.